2020
DOI: 10.1021/acs.jpcc.0c03649
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Oxygen Mobility in CePO4-Supported Catalysts: Mechanistic Implications on the Water–Gas Shift Reaction

Abstract: The hexagonal and monoclinic phases of CePO4 have demonstrated to be excellent catalytic supports for Ptbased WGS catalysts. Consequently, the elucidation of the WGS reaction mechanism in these materials constitutes a fundamental aspect in order to explain their catalytic behavior. Since the observed WGS reaction path is closely related to the absence or presence of oxygen vacancies in the support, the study of the oxygen mobility in these solids constitutes a key factor for the understanding of the materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…This showed that the residual H 2 O was stable and not removed by the thermal treatment (before DCM was introduced, the sample was purged at 400 °C in 20 vol % O 2 /Ar for 1 h), while the presence of DCM facilitated the release of adsorbed or structurally bound water molecules through their adsorption onto surface hydroxyl groups. More importantly, the intensity of these bands exhibited a significant decrease in the order h-CePi > Lm-CePi > Hm-CePi, which was in alignment with the inherent characteristics of these CePO 4 catalysts because more abundant structural H 2 O or surface hydroxyls were found on h-CePi. After the temperature increased to 200 °C, the singlet IR band at 1575 cm –1 was observed and ascribed to the carboxylate groups, besides the methyl group absorbance at 1360–1380 cm –1 , which indicated that the oxidative decomposition of DCM occurred. Figures d, S7, and S8 further display in situ DRIFTS of DCM decomposition in the presence of D 2 O.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…This showed that the residual H 2 O was stable and not removed by the thermal treatment (before DCM was introduced, the sample was purged at 400 °C in 20 vol % O 2 /Ar for 1 h), while the presence of DCM facilitated the release of adsorbed or structurally bound water molecules through their adsorption onto surface hydroxyl groups. More importantly, the intensity of these bands exhibited a significant decrease in the order h-CePi > Lm-CePi > Hm-CePi, which was in alignment with the inherent characteristics of these CePO 4 catalysts because more abundant structural H 2 O or surface hydroxyls were found on h-CePi. After the temperature increased to 200 °C, the singlet IR band at 1575 cm –1 was observed and ascribed to the carboxylate groups, besides the methyl group absorbance at 1360–1380 cm –1 , which indicated that the oxidative decomposition of DCM occurred. Figures d, S7, and S8 further display in situ DRIFTS of DCM decomposition in the presence of D 2 O.…”
Section: Resultsmentioning
confidence: 54%
“…13 The presence of the channels containing water in hexagonal CePO 4 led to an enhancement of the water−gas shift reaction owing to the increasing interaction with the water molecules, while the additional formation of monodentate formate and carbonate species could block the active sites on monoclinic CePO 4 due to the lower surface water content. 14,15 Hexagonal CePO 4 showed better NH 3 −SCR denitration activity and stability than monoclinic CePO 4 , which was attributed to the much stronger surface acidity and more surface-adsorbed oxygen species on the former. 16 Additionally, defect engineering is considered an excellent approach for tuning the physical and chemical properties due to the alteration in the material's composition, structural orientation, disordering, and lattice strain; various and abundant intrinsic defects (depending on its pristine structure or they can be introduced intentionally via thermal treatment, pH modification, size narrowing, and phase transition) are located in CePO 4 , such as Ce Frenkel (12.41 eV) > O Frenkel (11.02 eV) > Ce vacancy (9.09 eV) > O vacancy (6.69 eV), and their formation energies follow this trend (given in the decreasing order of energy).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of oxygen vacancies in CeZrO 4 is also well documented into the literature [38] . On the other hand, CePO 4 has a stable oxidation state of Ce III that cannot be oxidized to Ce (IV) thus limiting the oxygen mobility [39] …”
Section: Resultsmentioning
confidence: 68%
“…[38] On the other hand, CePO 4 has a stable oxidation state of Ce III that cannot be oxidized to Ce (IV) thus limiting the oxygen mobility. [39] In the present study, the catalytic activity of CePO 4 in terms of ammonia decomposition is relatively high compared to the other oxides possessing redox properties. So it is believed that the presence of defects in the structure does not play a key role in the decomposition of ammonia.…”
Section: Other Cerium-containing Samplesmentioning
confidence: 57%
“…The RWGS reaction (eq ) is commonly catalyzed with oxide-supported gold catalysts. Two main mechanisms are known: the redox mechanism and the associative mechanism. , The redox mechanism applies to Au nanoparticles supported on reducible supports, where CO 2 reoxidizes the partially reduced support, leading to the formation of CO. In the associative mechanism, CO is formed from the decomposition of formate species derived from the interaction of CO 2 with H 2 .…”
Section: Research In Catalysis With In Situ Uv–vis–nir Spectroscopymentioning
confidence: 99%